(untitled) (Jurnal Pendidikan Fisika, 2026)
Developing 21st-century competencies in physics education requires learning approaches that integrate scientific process skills, technological literacy, and creativity through meaningful and contextual experiences. However, vibration and sound wave learning is often presented abstractly, with limited connection to students’ cultural environments and minimal use of affordable technology for data acquisition. This study aims to develop and validate vibration- and sound-wave teaching materials using the traditional Sasak musical instrument, saron, integrated with low-cost information and communication technology (ICT) devices to enhance science process skills, technological literacy, and student creativity. The study employed a research and development approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Data were collected through field observations, document analysis, expert validation, and small-scale trials involving 11 prospective physics teachers. The developed teaching materials covered key vibration-wave concepts, including frequency, resonance, waveform analysis, harmonic structure, sound intensity, and creative musical instrument projects, supported by ICT tools such as Adobe Audition, LoggerPro, DaTuner, MacScope II, Advanced Spectrum, and intensity meter applications. The results indicate that the teaching materials were highly feasible, with an average validation score of 81.7% (good–very good), while user responses were very positive, with an average score of 399.91 out of 500. Empirical findings demonstrate that integrating the saron Sasak with ICT-based data acquisition enables students to connect abstract wave concepts with real phenomena, thereby strengthening inquiry skills, digital competence, and creative thinking. The novelty of this study lies in the comprehensive integration of local cultural instruments and affordable digital technologies into vibration-wave teaching materials that explicitly target multiple 21st-century skills within a TPACK-oriented framework. The study concludes that ethnoscience-based, ICT-integrated teaching materials are valid, practical, and effective for physics learning, advancing contextual, culturally responsive, and technology-enhanced physics education.